Materializing the Nation : Commodities, Consumption, and Media in Papua New Guinea - Foster, Robert John, 1957- (Book collections on Project MUSE., 2002)
""Foster shows us how seemingly banal activities like making a phone call, chewing betel nut, watching a Coke commercial may give important insights into the ways in which the nation is constructed, materialized or contested.""--Orvar Löfgren, author of On Holiday: A History of VacationingWhy, in the current era of globalization, does nationality remain an important dimension of personal and collective identities? In Materializing the Nation, Robert J. Foster argues that the contested process of nation making in Papua New Guinea unfolds not only through organized politics but also through munda.